Penerapan Komunikasi Verbal Bagi Anak Tunarungu Wicara Melalui Program Belajar Rubik Di Kotak Menara Bekasi - Alfi Nur Hayunida; Siti Nursanti; Rastri Kusumaningrum (KOMVERSAL, 2024)
Children with hearing and speech impairments are unable to hear due to hearing limitations, which also affects their ability to speak and use language. Therefore, children with hearing and speech impairments require intensive and consistent guidance in developing their communication skills, particularly verbal communication. The purpose of this research is to identify and understand how verbal communication is applied in the RUBIK learning program for children with special needs, especially those with hearing and speech impairments. This research uses a descriptive research method with a qualitative approach. The results show that the application of verbal communication for hearing-impaired children in the RUBIK program is a crucial aspect of the learning process. Teachers provide repeated verbal stimuli to help children become aware of sounds and practice their hearing and speaking abilities.